Hidden Persuaders: Do Small Gifts Lubricate Business Negotiations? - Maréchal, Michel André; Thöni, Christian (Management Science, 2019)
Gift-giving customs are ubiquitous in social, political, and business life. Legal regulation and industry guidelines for gifts are often based on the assumption that large gifts potentially influence behavior and create conflicts of interest, but small gifts do not. However, scientific evidence on the impact of small gifts on business relationships is scarce. We conducted a natural field experiment in collaboration with sales agents of a multinational consumer products company to study the influence of small gifts on the outcome of business negotiations. We find that small gifts matter. On average, sales representatives generate more than twice as much revenue when they distribute a small gift at the onset of their negotiations. However, we also find that small gifts tend to be counterproductive when purchasing and sales agents meet for the first time, suggesting that the nature of the business relationship crucially affects the profitability of gifts. This paper was accepted by John List, behavioral economics.